1995
DOI: 10.1007/bf02246159
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic mechanisms of cocaine effects in humans

Abstract: The objective of this study was to investigate the role of serotonin (5-HT) in mediating the effects of cocaine in humans. To accomplish this, 12 subjects each participated in two randomized, double-blind test sessions separated by 1 week. In one session, subjects underwent acute depletion of the 5-HT amino acid precursor tryptophan (TRP), followed by a test dose of intranasal cocaine. In the other session, the cocaine test dose was preceded by sham depletion. Subject ratings of cocaine "high" were significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(45 citation statements)
references
References 43 publications
2
42
1
Order By: Relevance
“…Finally, while serotonin may modulate risky choices through its influences upon learning from negative outcomes (Evers et al, 2005; see below), it is also likely that serotonin can alter choice behaviors via processing of positive reward signals when making decisions, consistent with the evidence of functional interactions between midbrain dopamine neurones and the serotonergic neurones of the raphe (Nakamura et al, 2008) and evidence that serotonin activity can facilitate aspects of dopaminemediated reward processing (Aronson et al, 1995). Thus, Rogers et al (2003) showed that tryptophan depletion reduced healthy volunteers' attentional processing of reward cues, but not probability or punishment cues, when deciding between risky actions associated with uncertain outcomes, highlighting a role for serotonin in auxiliary cognitive activitiesFthis time, attentionalFin decisionmaking functions .…”
Section: Serotonin and Risky Choicementioning
confidence: 85%
See 1 more Smart Citation
“…Finally, while serotonin may modulate risky choices through its influences upon learning from negative outcomes (Evers et al, 2005; see below), it is also likely that serotonin can alter choice behaviors via processing of positive reward signals when making decisions, consistent with the evidence of functional interactions between midbrain dopamine neurones and the serotonergic neurones of the raphe (Nakamura et al, 2008) and evidence that serotonin activity can facilitate aspects of dopaminemediated reward processing (Aronson et al, 1995). Thus, Rogers et al (2003) showed that tryptophan depletion reduced healthy volunteers' attentional processing of reward cues, but not probability or punishment cues, when deciding between risky actions associated with uncertain outcomes, highlighting a role for serotonin in auxiliary cognitive activitiesFthis time, attentionalFin decisionmaking functions .…”
Section: Serotonin and Risky Choicementioning
confidence: 85%
“…For example, the behavioral and reinforcing effects of cocaine in rats are potentiated by treatment with selective serotonin-reuptake blockers (SSRIs) (Cunningham and Callahan, 1991;Kleven and Koek, 1998;Sasaki-Adams and Kelley, 2001), and brain self-stimulation thresholds can also be dose dependently altered with SSRI treatment (Harrison and Markou, 2001). Similarly, tryptophan depletion can block the rewarding effects of cocaine in human subjects (Aronson et al, 1995).…”
Section: Background: Dopamine and Serotonin In Reinforcement Processingmentioning
confidence: 99%
“…More directly, tryptophan depletion has been shown to diminish the euphoric effects of intravenous cocaine in cocaine addicts (Aronson et al, 1995), and to reduce the craving experienced when presented with cocaine-related paraphernalia (Satel et al, 1995). The latter finding suggests that serotonin affects the way that reward-associated signals influence behaviour; consistent with reports that fluoxetine potentiates the control of ongoing responding by available conditioned reinforcers (Sasaki-Adams and Kelley, 2001;Fletcher et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…When patients were exposed to cocaine-related paraphernalia (specifically intended to enhance craving), RTD diminished the subjective feelings of craving (Satel et al 1995). In another group of addicts, RTD diminished the "high" feeling after intranasal cocaine when compared with sham challenge (Aronson et al 1995). Since serotonergic raphe neurons are known to modulate mesolimbic dopaminergic reward pathways believed to mediate the rewarding properties of all known drugs of abuse (Baumgarten and Grozdanovic 1994), these findings imply that RTD directly reduces the pleasurable subjective states related to drug craving and drug reward.…”
Section: Other Psychiatric Diagnosesmentioning
confidence: 90%